2009
DOI: 10.1111/j.1439-0396.2008.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isovalerate on ruminal fermentation, urinary excretion of purine derivatives and digestibility in steers

Abstract: The objective of this study was to evaluate the effects of isovalerate supplementation on rumen fermentation, urinary excretion of purine derivatives and feed digestibility in the total tract of steers. Eight ruminally cannulated Simmental steers were used in a replicated 4 · 4 Latin square experiment. The treatments were: control (without isovalerate), low isovalerate (LIV), medium isovalerate (MIV) and high isovalerate (HIV) dosage of isovalerate at 100, 200 and 300 mg isovalerate per kg dry matter (DM) inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 31 publications
(50 reference statements)
14
47
1
Order By: Relevance
“…In this study, total branched-chain VFA yields linearly increased as the supplemental amount of BCAA was increased. Several studies have shown that ruminal fermentation is stimulated and fiber digestion is enhanced by BCVFA supplementation (Liu et al, 2009), further proving that valine or isoleucine supplementation has a tendency to increase the degradation of wheat straw in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, total branched-chain VFA yields linearly increased as the supplemental amount of BCAA was increased. Several studies have shown that ruminal fermentation is stimulated and fiber digestion is enhanced by BCVFA supplementation (Liu et al, 2009), further proving that valine or isoleucine supplementation has a tendency to increase the degradation of wheat straw in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that BCVFA can improve apparent dry matter digestibility and microbial growth, and enhance microbial functions and enzyme activities in the rumen of sheep (Andries et al, 1990; Moharrery, 2004). Dietary supplementation with BCVFA improves rumen fermentation and enhances digestion of cattle (Liu et al, 2008, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The ruminal degradability of feed fibre is closely related to the concentration of ruminal acetate and fibre digestion in the total tract (Liu et al, 2009a;Wang et al, 2009). The quadratic increase in ruminal degradability of NDF of corn silage with increasing PRFA supplementation was in accordance with the increased ruminal enzyme activity, populations of ruminal cellulolytic bacteria, and resulted in the quadratic increased ruminal total VFA and molar ratio of acetate.…”
Section: Ruminal Degradabilitymentioning
confidence: 60%
“…Because BCFAs are generated principally from amino acids, their formation by colonic bacteria provides a useful marker of protein digestion in the large intestine of human (Macfarlane & Macfarlane, ), suggesting that fungi in the hindgut of piglets may probably be highly related to the protein digestion. BCFAs also have been extensively studied in ruminants and proved to be necessary for the growth of ruminal cellulolytic bacteria, such as Ruminococcus albus and Ruminococcus flavefaciens (Liu et al, ; Wang et al, ). In view of that, our results indicate that fungi in the hindgut of the piglets may be associated with the activity of fibre degrading bacteria, which in turn, may be involved in the utilization of complex carbohydrates in the diet.…”
Section: Discussionmentioning
confidence: 99%